Prolonged postoperative ileus after elective colorectal cancer surgery - Nestorović, Milica; Stanojević, Goran; Branković, Branko; Pecić, Vanja; Jeremić, Ljiljana (Vojnosanitetski pregled, 2020)
Background/Aim. Postoperative ileus is a frequent and frustrating occurence for both, patients and surgeons after abdominal surgery. Besides clinical importance of postoperative ileus, its economic aspect is also important. The aim of this prospective study was to analyze development of prolonged postoperative ileus after elective colorectal surgery for cancer and its impact on early postoperative outcome. Methods. This prospective study included all eligible patients, 18 years or older, scheduled for open colorectal resection for cancer from June, 2015 to February, 2016. Patients with metastatic disease, prior hemoirradiation or any resection other then curative were excluded. The study duration was up to 30 days postoperatively. Primary outcome measure was development of prolonged postoperative ileus according to strict definition. The impact of prolonged postoperative ileus on other outcome measures such as postoperative complications, surgical site infections, anastomotic leakage, reoperations, mortality and length of hospital stay were of great interest, too. Results. This prospective study included 103 patients, 64 (37.9%) men and 39 (62.1%) women, mean age 66 years. Prolonged postoperative ileus developed in 12 (11.3%) patients. One third of the patients had some type of surgical site infection, while 47.6% had complications. Ten (9.7%) patients required reoperation. Comparing the group of patients with prolonged postoperative ileus with those without, there were no statistically significant differences in rates of surgical site infection and anastomotic leakage. There was statistically significant difference in terms of complications (χ2 = 34.966; p < 0.001), complications grade III (χ2 = 23.43; p < 0.001) and reoperations (χ2 = 15.724; p
Keywords: colorectal neoplasms; postoperative complications; ileus; digestive system surgical procedures; elective surgical procedures; risk factors.